A scoping review to ascertain the parameters for an evidence synthesis of psychological interventions to improve work and wellbeing outcomes among employees with chronic pain. Issue 1 (1st January 2021) - McParland, Joanna L.; Andrews, Pamela; Kidd, Lisa; Williams, Lynn; Flowers, Paul
ABSTRACT: Background: Psychological interventions have mixed effects on improving employee outcomes, partly due to significant variability across studies and a lack of focus on mechanisms of action. This scoping review reports on the parameters of these interventions and examines intervention content to bring clarity to this heterogeneous topic area and direct future systematic review work. Method: Six databases were searched (Cinahl, Cochrane, Embase, Medline, PsychINFO and Web of Science) from April 2010 to August 2020, and a grey literature search was undertaken. Screening was undertaken independently by two authors. The results summarised country, participant and employment characteristics, psychological interventions and work, health and wellbeing outcomes. 10% of the papers were analysed to determine the feasibility of coding intervention descriptions for theory and behaviour change technique (BCT) components. Results: Database searches yielded 9341 titles, of which 91 studies were included. Most studies were conducted in Europe (78%) and included males and females (95%) ranging in age from 31-56.6 years although other demographic, and employment information was lacking. Musculoskeletal pain was common (87%). Psychological interventions commonly included cognitive behavioural therapy (30%) and education (28%). Most studies employed a randomised control trial design (64%). Over half contained a control group (54%). Interventions were delivered in mostly healthcare settings (72%) by health professionals. Multiple outcomes were often reported, many of which involved measuring sickness absence and return-to-work (62%) and pain and general health (53%). Within the feasibility analysis, most papers met the minimum criteria of containing one paragraph of intervention description, but none explicitly mentioned theory or BCTs. Conclusion: Psychological interventions for employees with chronic pain vary in their nature and implementation. We have shown scoping reviews can be used to assess the feasibility of applying tools from health psychology to identify the content of these interventions in future systematic review work to improve intervention development.